The Formation of Residual Lithium Compounds on Ni‐Rich NCM Oxides: Their Impact on the Electrochemical Performance of Sulfide‐Based ASSBs - Aktekin, Burak; Sedykh, Alexander E.; Müller‐Buschbaum, Klaus; Henss, Anja; Janek, Jürgen (Advanced functional materials, 2024)
Residual lithium compounds (RLCs) are known to form on the surface of nickel‐rich LiNi1‐x‐yCoxMnyO2 (NCM) oxides during synthesis and storage. In this study, the impact of RLCs on cathode performance in sulfide‐based all‐solid‐state batteries (ASSBs) is investigated by employing practically relevant approaches to generate (or remove) RLCs on (or from) NCM single crystal particles. It is revealed that Li2CO3 is the predominant component in samples exposed to air. Surprisingly, heat treatment at high temperatures does not remove RLCs but increases the overall RLC content, accompanied by the partial transformation of existing RLCs into Li2O. These samples exhibit compromised electrochemical performance due to asymmetric overpotential increase during cell discharge. However, it is possible to recover performance through controlled ambient air storage which enables the conversion of existing Li2O into Li2CO3 and formation of fresh Li2CO3 on the surface. Notably, the beneficial effects are not replicated with pure CO2 or moisturized air storage, emphasizing the significance of storage conditions and reaction pathways for Li2CO3 formation. This study demonstrates that removal of Li2O residuals through the formation of Li2CO3 under controlled ambient air exposure proves to be advantageous for sulfide‐based ASSBs, thereby offering valuable guidance for the development of optimized NCM‐based ASSB systems. This study reveals that Li2CO3 is the predominant residual lithium compound (RLC) forming on nickel‐rich NCM oxides exposed to air. High temperature annealing increases the overall RLC content due to transformation of existing RLCs into Li2O. Li2O‐rich samples exhibit compromised electrochemical performance in ASSBs due to high resistance and asymmetric overpotential. Ambient air storage transforms Li2O back to Li2CO3 and recovers the performance. These findings offer valuable guidance for the development of optimized NCM‐based ASSB systems.